The Influence of Creativity and Skills on Business Success in East Jakarta SMEs - Amalia, Ira (Global Insights in Management and Economic Research, 2025)
Purpose of the study: This research aims to investigate the relationships between creativity, skills, and business success in SMEs. Specifically, it examines how creativity influences skill development, how skills impact business success, and the combined effect of both creativity and skills on the overall success of SMEs in East Jakarta. Materials and methods: A quantitative approach was used, employing a survey method to collect data from 93 SME owners and managers in the Cakung District of East Jakarta. The research model explored causal relationships using creativity and skills as independent variables, and business success as the dependent variable. Data was analyzed through path analysis using SPSS, testing hypotheses and evaluating model fit. Results: The study found significant positive relationships between creativity, skills, and business success. Specifically, creativity positively influenced both skill development (β = 0.47) and business success (β = 0.38). Additionally, skills were shown to have a significant positive impact on business success (β = 0.42). The combined effect of creativity and skills explained 58% of the variance in business success. Conclusions: This study provides valuable insights into the role of creativity and skills in SME success. The findings suggest that a dual focus on enhancing creativity and technical skills can significantly improve the performance and sustainability of SMEs. Future research should explore the mechanisms through which creativity influences skill development and investigate these relationships across different sectors and regions.